China’s role in global marine conservation: opportunities and challenges in implementing ABMTs in ABNJ under the BBNJ Agreement - Miao, Xiaojing; Chen, Li (Frontiers in Marine Science, 2025)
Area-based management tools (ABMTs) are crucial for conserving marine biodiversity in areas beyond national jurisdiction (ABNJ). The BBNJ Agreement establishes a global framework for the protection of critical ocean areas through implementing ABMTs. While this agreement provides a global framework, its success relies on individual states’ participation and dedication. China has signed the BBNJ Agreement, recognizing the essential role of this global framework in coordinating international efforts to implement ABMTs. This article argues that China possesses capabilities to advance ABMTs in ABNJ, drawing from its established national policies, institutional framework, international collaboration, and extensive experience managing domestic marine protected areas (MPAs). However, to reinforce its contribution to global marine conservation, China needs to overcome key challenges. These include enhancing domestic legislation to better align with BBNJ Agreement, and building expertise in implementing ABMTs in ABNJ.